Pengaruh Disiplin Kerja, Budaya Organisasi dan Komunikasi terhadap Kinerja Karyawan CV. Tanjidor - Nadia Vega; Sri Wahyuningsih (Departement of Mathematics Education, 2023)
Employee performance is a real attitude shown by employees as work performance that is produced according to their role in the company. High performance for employees will reduce absenteeism due to laziness, and make the work given or assigned to them more optimal. This study aims to determine the effect of work discipline, organizational culture, and communication on the performance of CV employees. Tanjidor. The type of research used is quantitative. With a population of CV.Tanjidor employees and sampling with saturated sampling technique with a sample of 84 respondents. The analysis technique for this research used Structural Equation Modeling (SEM) with the Lisrel 8.80 program. The analytical method used is validity test, reliability test, classical assumption test and multiple linear regression analysis.